2021
DOI: 10.1002/mp.15373
|View full text |Cite
|
Sign up to set email alerts
|

Superiorization versus regularization: A comparison of algorithms for solving image reconstruction problems with applications in computed tomography

Abstract: A system matrix can be built in order to account for the refractions in an optical computed tomography (CT) system. In order to utilize this system matrix, iterative methods are employed to solve the image reconstruction problem. The purpose of this study is to compare potential iterative algorithms to solve this image reconstruction problem. Comparisons examine both solution time and the quality of the reconstructed image. While our work is motivated by optical CT, the results can be extended more generally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The reconstruction algorithms that were investigated were the top 6 performing algorithms set forth by Guenter et al [41] with the addition of the Landweber [32] algorithm to be used as a baseline for comparison. These algorithms are summarized in table 1.…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reconstruction algorithms that were investigated were the top 6 performing algorithms set forth by Guenter et al [41] with the addition of the Landweber [32] algorithm to be used as a baseline for comparison. These algorithms are summarized in table 1.…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
“…In contrast, SIRT algorithms use all the equations at the same time in one iteration, hence being termed simultaneous. Guenter et al [41] evaluated a collection 21 SIRT algorithms in terms of solution error, total variation and run time. The analysis was intended to compare a large number of algorithms on a large number of test problems with varying image properties and noise levels to determine the top-performing algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system matrix used in the iterative reconstructing algorithm is built in-house and based on the ray-tracing simulator created for the scanner design optimization (Ogilvy et al 2020). In 2021, Guenter et al identified several viable algorithms for CT imaging (Guenter et al 2022). Of those, the FISTA has high performance when a stopping condition is unknown, and can be run to higher number of iterations without fear of over-iterating.…”
Section: Reconstructionmentioning
confidence: 99%
“…clinical test problems by Guenter et al in 2021, and FISTA-TV was a top performer in both solution quality and low runtime[14].…”
mentioning
confidence: 95%